Inovasi Pot Biodegradable Berbasis Jerami Padi sebagai Solusi Alternatif Pengganti Pot Plastik Ramah Lingkungan - Agil Raihan Majid; Aulia Wahyu Nur Saputri; Dinda Aulia Dwianjani; Jedidiah Donniar Yajnavido; Karin Nadia Kurniawan; Nabila Triana; Putri Faliza Sulistyawati; Rizka Preti Febriana; Rosa Estri Kinasih; Thirza Amaris Gusma (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
The use of plastic as planting containers remains a serious environmental issue due to its non-biodegradable nature, which can contaminate soil and water. One solution is to utilize rice straw waste as a raw material for biodegradable pots. This innovation can reduce dependence on plastic pots while providing ecological and economic benefits. Rice straw-based pots offer several advantages, including easy decomposition in soil, enhancing soil fertility, and reducing pollution caused by straw burning. This study aims to utilize rice straw waste to produce environmentally friendly biodegradable pots as an alternative to plastic containers. The method employed is Participatory Action Research (PAR), emphasizing collaboration between students and teachers through hands-on learning. The activities include socialization, practical training on making rice straw pots, participatory evaluation, and the use of the pots as planting media. The results showed that 100% of participants successfully produced high-quality rice straw pots, with positive responses reflected in high satisfaction and increased understanding of recycling concepts. The rice straw pots decompose within 2–3 months, add organic matter to the soil, and create opportunities for a circular economy. The main challenge identified is the relatively short durability of the pots, requiring innovations using natural adhesives or material combinations to enhance resilience. These findings reinforce the potential of rice straw as a solution for agricultural waste management and community empowerment toward sustainable agriculture.